Pengaruh Pertumbuhan Ekonomi, Jumlah Industri dan Pendidikan Terhadap Tingkat Pengangguran Terbuka di Kabupaten Sidoarjo - Septiana, Marwah; Asmara, Kiky (Universitas Hamzanwadi, 2024)
Sidoarjo Regency, with the highest unemployment rate in East Jawa, is in the spotlight because it has the potential to hinder regional progress. This study aims to identify the effect of economic growth, the number of industries, and education on the open unemployment rate in Sidoarjo district for the period 2014–2023. Secondary and time series data from BPS East Java and Sidoarjo districts were analyzed using multiple linear regression on IBM SPSS Statistic 25 software. The research findings show that economic growth has a negative and significant relationship with the open unemployment rate, while the number of industries has no influence and education has a negative but insignificant relationship.